2016
DOI: 10.1021/acs.iecr.6b02452
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Synthesis of Isoprene from Methyl tert-Butyl Ether and Formalin Using Keggin-Type Heteropolyacids

Abstract: A liquid-phase single-stage synthesis of isoprene from methyl tert-butyl ether (MTBE) and formalin using Keggin-type heteropolyacids, phosphotungstic acid (PTA), phosphomolybdic acid (PMA), and silicotungstic acid (STA) was performed in a batch reactor. The effects of catalyst concentration, reaction temperature, MTBE/formaldehyde ratio, and solvent type on isoprene yield were evaluated. At moderate reaction conditions, the two-phase organic−aqueous system with cyclohexane addition and high MTBE/formaldehyde r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Unfortunately, the yield of 3a gradually decreased after each cycle. The polymerization of isoprene could not be avoided in the presence of the strong acid at high temperatures [53][54][55][56][57]. Thus, after several runs under the optimized conditions, the accumulated coke on the surface of Nafion led to its diminished catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the yield of 3a gradually decreased after each cycle. The polymerization of isoprene could not be avoided in the presence of the strong acid at high temperatures [53][54][55][56][57]. Thus, after several runs under the optimized conditions, the accumulated coke on the surface of Nafion led to its diminished catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, additional studies on the synthesis of isoprene by alternative routes have been reported. Songsiri et al [72,73] synthesized isoprene using heteropolyacids as catalysts in a liquid-phase system under moderate conditions in which carbon deposits can be inhibited. Methyl tertiary-butyl ether (MTBE) was used as the source of isobutene.…”
Section: Synthesis Of Isoprenementioning
confidence: 99%
“…The total selectivities of 4,4-dimethyl-1,3-dioxane (3) and 3-methyl-1,3-butanediol (4) are above 98% throughout the temperature range (60-150 °C) investigated. No dehydration products (such as 3-methyl-butenol isomers and isoprene) [22,34] derived from 3-methyl-1,3-butanediol, which are usually obtained via vapor-phase dehydration at high temperatures (≥300 °C), were observed. In our catalytic system, the reactions were conducted at liquid phase (Reaction temperature ≤ 150 °C) and in water, which did not favor the dehydration of 3-methyl-1,3-butanediol.…”
Section: Effect Of Reaction Temperaturementioning
confidence: 99%
“…In the synthesis route, both the Prins condensation and hydrolysis reaction require acid catalysts [3,15,16]. Various solid acid catalysts, such as metal oxide catalysts [17], zeolite catalysts [18], phosphate catalysts [15,19,20], and heteropolyacids catalysts [21,22], have been developed for the two-step reaction (Prins condensation and hydrolysis reaction). Alternatively, a single-stage 3-methyl-1,3-butanediol synthesis from isobutene and HCHO in water is one interesting route to be investigated, and a water-tolerant acid catalyst is critical.…”
Section: Introductionmentioning
confidence: 99%